THE POLITICAL DISCOURSE IN VENEZUELA OF HUGO CHÁVEZ: REFORM OF THE AMENDMENT TO THE CONSTITUTION (2007-2009) - Romero J., Juan Eduardo (2013)
In this paper, is raised from the approaches of political theory and discourse analysis, the construction of political discourse on constitutional reform proposed by Venezuelan President Hugo Chávez in January 2007, and that meant a generation of political debate on the implications and impact which Venezuelan society could have. Identified the political protagonists and antagonists involved, their plots and expository speeches that explains his position to accept or reject the proposed reform. It concludes by stating that the result was the product of a culture shock on the perceptions of political change in Venezuela.